Karst paleotopography on top of the Dengying Formation and petroleum geological significance in the Central Sichuan Basin, China. Issue 2 (March 2023) - Zhou, Zikun; Wang, Xingzhi; Yang, Xiyan; Wang, Wenzhi; Zhou, Hongfei; Yang, Yueming; Wen, Long; Huo, Fei; Pei, Senqi
Reconstructing karst palaeogeomorphology is a useful approach to identifying target areas for oil and gas exploration. This study used the elevation method to reconstruct the karst palaeogeomorphology at the top of the 4th member (Z2 dn 4 ) of the Dengying Formation (Z2 dn) in the Central Sichuan Basin based on 2D and 3D seismic and drilling data. The bottom of the Longwangmiao Formation and the top of the 2nd member (Z2 dn 2 ) of the Z2 dn were optimized as the upper and lower base levels, respectively. The reconstructed palaeogeomorphology was divided into five types – slopes, erosional peneplains, monadnocks, domes and depressions – according to their morphology, scope and gradient, allowing inference of the palaeohydrological conditions. Slopes were subdivided into gentle (<1.2°) and steep (≥ 1.2°; maximum gradient around 16°). Reservoirs on steep slopes and monadnocks are the most developed, owing to their considerable hydraulic head differences, strong palaeohydrodynamics, and intense erosion and incision. Steep slopes with more developed karst porosities are banded and immediately adjoin a regional hydrocarbon generation centre. Hydrocarbons generated in this centre tend to migrate laterally and become entrapped in porous slopes and their vicinities. Consequently, hydrocarbons move upward along steep slopes and, preferentially, slopes and monadnocks. Thus, the steep slope zone and its vicinity (including some monadnocks, gentle slopes and peneplains) are the most favourable areas for exploration of hydrocarbon reservoirs and should be the primary targets.